2008
DOI: 10.1186/1748-5908-3-32
|View full text |Cite
|
Sign up to set email alerts
|

The uptake and effect of a mailed multi-modal colon cancer screening intervention: A pilot controlled trial

Abstract: Background: We sought to determine whether a multi-modal intervention, which included mailing a patient reminder with a colon cancer decision aid to patients and system changes allowing direct access to scheduling screening tests through standing orders, would be an effective and efficient means of promoting colon cancer screening in primary care practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 20 publications
0
52
0
Order By: Relevance
“…5 New quality measures that assess how well physicians actually engage patients in the decision-making process, as called for in the Affordable Care Act, are urgently needed to help eliminate such counterproductive beliefs and practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 New quality measures that assess how well physicians actually engage patients in the decision-making process, as called for in the Affordable Care Act, are urgently needed to help eliminate such counterproductive beliefs and practices.…”
Section: Discussionmentioning
confidence: 99%
“…2 Studies have shown that patients' preferences for specific methods of colorectal cancer screening vary, and the use of decision aids on this topic has been linked to increases in screening rates. 5 However, there is evidence that despite physi- …”
mentioning
confidence: 99%
“…Other studies have mailed DVDs, 8,9,17,18 and some have also encouraged group discussions regarding PSA screening. 11,12 However, our study is larger than these previous studies and was performed in a more generalizable population in two settings in the US.…”
Section: Discussionmentioning
confidence: 98%
“…To date, our study is the first study that estimates the costs and cost-effectiveness of a patient-directed intervention (mailed educational reminder) on CRC screening among U.S. Veterans at average risk of developing CRC. Prior studies on cost-effectiveness of patient-directed interventions for CRC screening have shown mixed results (Table 4), with costs ranging from $43 to $5842 per additional individual screened for CRC [17,18,20,27]. In one study, Lairson and colleagues randomized their patients who received FOBT and flexible sigmoidoscopy (FS) referrals to either two rounds of mailed reminders, two rounds of tailored mailed reminders, or two rounds of reminder telephone calls along with the tailored mailed reminder [18].…”
Section: Discussionmentioning
confidence: 99%
“…Given the highly constrained resources for health promotion, it is essential for decision makers to require information on the costs and cost-effectiveness of the interventions. Although there have been several studies on the economics of cervical cancer and mammography screening promotion [13,14], few studies have evaluated the cost-effectiveness of patient or providerdirected interventions for CRC screening in average risk patients, especially in the VA population [15][16][17][18][19][20]. The primary aim of this study is to assess the costs and costeffectiveness of our mailed educational reminder on adherence with FOBT-type screening among the U.S.…”
Section: Introductionmentioning
confidence: 99%